2001
DOI: 10.1093/cercor/11.3.260
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dorsolateral Prefrontal Cortex in the Preparation of Forthcoming Actions: an fMRI Study

Abstract: The dorsolateral prefrontal cortex (DLPFC) plays a key role in working memory (WM). Yet its precise contribution (the storage, manipulation and/or utilization of information for the forthcoming response) remains to be determined. To test the hypothesis that the DLPFC is more involved in the preparation of actions than in the maintenance of information in short-term memory (STM), we undertook a functional magnetic resonance imaging investigation in normal subjects performing two delayed response tasks (matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
164
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(179 citation statements)
references
References 28 publications
13
164
0
2
Order By: Relevance
“…Although the dorsal PM has therefore often been related to sequential complexity in general, this interpretation is rendered implausible by the finding that increasing sequential complexity in nonspatial sequences, such as size-based and pitch sequences, particularly engages ventral premotor areas (Schubotz and von Cramon, 2002a,b). Moreover, dorsal PM engagement in spatial processing has been reported more generally in nonsequential paradigms in humans (Griffiths et al, 2000;Nobre et al, 2000;Lamm et al, 2001;Pochon et al, 2001;Vingerhoets et al, 2002;Handy et al, 2003). This is in line with a contribution of nonhuman primate dorsal PM to spatial tasks in general, not only sequential ones (Kubota and Hamada, 1978;Passingham, 1987;Boussaoud and Wise, 1993;Shen and Alexander, 1997;Boussaoud, 2001;Lebedev and Wise, 2001).…”
Section: Discussionsupporting
confidence: 65%
“…Although the dorsal PM has therefore often been related to sequential complexity in general, this interpretation is rendered implausible by the finding that increasing sequential complexity in nonspatial sequences, such as size-based and pitch sequences, particularly engages ventral premotor areas (Schubotz and von Cramon, 2002a,b). Moreover, dorsal PM engagement in spatial processing has been reported more generally in nonsequential paradigms in humans (Griffiths et al, 2000;Nobre et al, 2000;Lamm et al, 2001;Pochon et al, 2001;Vingerhoets et al, 2002;Handy et al, 2003). This is in line with a contribution of nonhuman primate dorsal PM to spatial tasks in general, not only sequential ones (Kubota and Hamada, 1978;Passingham, 1987;Boussaoud and Wise, 1993;Shen and Alexander, 1997;Boussaoud, 2001;Lebedev and Wise, 2001).…”
Section: Discussionsupporting
confidence: 65%
“…Several studies comparing delay epochs with and without manipulative requirements report that although the DLPFC is active during maintenance, it is significantly more active when manipulation is also required (Wagner et al, 2001), even when the tasks are matched for difficulty Postle et al, 1999). One study reported DLPFC activity when subjects had to prepare a sequential action during the delay, but not during simple maintenance (Pochon et al, 2001). However, another study found that DLPFC activity was present during maintenance even when no decision or response was required (Wagner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Newer studies are beginning to emphasize processes further down stream in the perception-action cycle, such as response selection, motor preparatory set, and memoryguided actions [61][62][63][64][65]. For example, Pochon et al [66] reported DLPFC activation during the delay only when subjects mentally prepared for an upcoming memoryguided sequence of actions and not when they simply maintained the visuospatial information. This result suggests that the sustained delay period activity often imaged cannot be interpreted solely as a signature of actively stored representations.…”
Section: Atop the Motor Hierarchymentioning
confidence: 99%